Sensitivity of Grapevine Phenology to Water Availability, Temperature and CO2 Concentration - Martínez-Lüscher, Johann; Kizildeniz, Tefide; Vučetić, Višnja; Dai, Zhanwu; Luedeling, Eike; van Leeuwen, Cornelis; Gomès, Eric; Pascual, Inmaculada; Irigoyen, Juan J.; Morales, Fermín; Delrot, Serge (Frontiers in Environmental Science, 2016)
In recent decades, mean global temperatures have increased in parallel with a sharp rise in atmospheric carbon dioxide (CO2) levels, with apparent implications for precipitation patterns. The aim of the present work is to assess the sensitivity of different phenological stages of grapevine to temperature and to study the influence of other factors related to climate change (water availability and CO2 concentration) on this relationship. Grapevine phenological records from 9 plantings between 42.75°N and 46.03°N consisting of dates for budburst, flowering and fruit maturity were used. In addition, we used phenological data collected from two years of experiments with grapevine fruit-bearing cuttings with two grapevine varieties under two levels of water availability, two temperature regimes and two levels of CO2. Dormancy breaking and flowering were strongly dependent on spring temperature, while neither variation in temperature during the chilling period nor precipitation significantly affected budburst date. The time needed to reach fruit maturity diminished with increasing temperature and decreasing precipitation. Experiments under semi-controlled conditions revealed great sensitivity of berry development to both temperature and CO2. Water availability had significant interactions with both temperature and CO2; however, in general, water deficit delayed maturity when combined with other factors. Sensitivities to temperature and CO2 varied widely, but higher sensitivities appeared in the coolest year, particularly for the late ripening variety, ‘White Tempranillo’. The knowledge gained in whole plant physiology and multi stress approaches is crucial to predict the effects of climate change and to design mitigation and adaptation strategies allowing viticulture to cope with climate change.